Reviewing Montesquiue's Thoughts on Trias Politica and Its Relevance to Article 6A paragraph (2) of the 1945 Constitution of the Republic of Indonesia: Securing Freedom and Preventing Authoritarianism - Alvian Tresna Chariza; Moh. Indra Bangsawan (Universitas Muhammadiyah Surakarta, 2023)
Many legal researchers have published studies on Trias Politica, but few have applied it clearly in government and democratic systems, especially in Indonesia which has a mixed government system, namely the Presidential System and the Multiparty System which are regulated clearly in Article 6A paragraph (2) of the 1945 Constitution. , which causes uncertainty in government practices in Indonesia. This research aims to review how the concept of separation of powers in Montesquieu's Trias Politica develops in the legal and government system in Indonesia. This research uses a doctrinal method with a statutory and conceptual approach. The research results show that Indonesia has not implemented the Trias Politica concept firmly, and the application of Article 6A paragraph (2) has the potential to lead to abusepower.